The Modern Theory of Finance: Suggestions for an Overall Vision - Carlo D'Adda (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
Traditionally the term "finance" has been used to indicate the art of raising funds to realize both public and private spending programs.
Keywords: 330